Sosialisasi Dampak Sosial pada Masyarakat Lingkar Kawasan Ekonomi Khusus (KEK) Kabupaten Sorong - Bustamin Wahid; Yuliana A; Siti Nurl Nikmatul Ulu; Rosnani Rosnani; Agil Saeni (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
This socialization aims to increase the knowledge of the people around the Special Economic Zone (KEK) by using a persuasive approach for the Kokoda community in the KEK of Sorong Regency, the infrastructure of this activity can be seen from two things, namely the impact of the socio-economic community and the level of community awareness around the KEK of Sorong Regency. Therefore, it is important for the process of building public awareness to face open competition in special economic zones in the future. This socialization is used with a persuasive approach to the leaders of Kokoda in the area around the KEK. One reason for this approach is that it is much more effective than a collective movement. Because the social basis of society is still very strong with social patrons, it is important that we use a persuasive approach.